Clinic and diagnosis and comorbidity of respiratory tuberculosis and viral pneumonia caused by Herpes simplex virus, Cytomegalovirus Human and SARS-CoV-2 in patients with late-stage HIV infection with immunodeficiency - Vladimir Yu. Mishin; Anastasiia V. Mishina; Dmitry A. Lezhnev; Aleksandr L. Sobkin; Ivan V. Shashenkov (Consilium Medicum, 2022)
Aim. To study the features of the social status, clinic and diagnosis of respiratory tuberculosis comorbidity and viral pneumonia caused by Herpes simplex virus type 1, Cytomegalovirus Human and SARS-CoV-2 in patients with late-stage HIV infection with immunodeficiency.